„Uspokojona, uspokajająca... Elegia młodopolska jako ogniwo modernistycznych dziejów gatunku - Czabanowska-Wróbel, Anna (Przestrzenie Teorii, 2007)
This dissertation shows synthetically the Young Poland elegy together with a proposal, due to properties of aesthetics and subject matter of the typology of the genre in this epoch: 1. elegies of the mood connected with the poetics of symbolism, which instead of a personal confession, contain picturesque equivalents of "the condition of soul", 2. autobiographical elegies, among them elegies of memories, 3. stylised elegies, consciously formed according to old genre models. What has been emphasised is the importance of the genre and its unbroken continuity between the 19th and 20th centuries. The most important role was played by the autobiographical elegy in which Leśmian achieved mastery, which aimed from the personal confession to psychological and epistemological discoveries. Staff's role is important as he practised all three kinds of elegy. The wide-ranging phenomenon of elegiacness, occurring also in prose, has been signalled.